Effects of Transcranial Stimulation on Resistance Exercise in Mentally Fatigued Subjects - Solon-Júnior, Luiz José Frota; Lima-Júnior, Dalton; Roelands, Bart; Boullosa, Daniel; Ferreira, Maria Elisa Caputo; Fortes, Leonardo De Sousa (International Journal of Sports Medicine)
The objective was to analyze the effect of Anodic transcranial direct current stimulation (a-tDCS) over the the primary motor cortex (M1) on resistance exercise in mentally fatigued individuals. Thirty-five participants performed a Stroop task (ST) to induce mental fatigue (MF) until they reached 50 mm on the visual analogue scale under three different conditions in a randomized, double-blind, crossover experimental trial. The participants completed a resistance training (RT) session with six sets for muscle failure with fixed load (Vload 1 m.s.-1) after ST. During the RT session, performance parameters as the maximum number of repetitions (MNR), power output, and bar velocity were recorded with linear encoder. Muscle activation (sEMG) and rating of perceived exertion (RPE) were also measured throughout the RT session. The MNR, mean power output, and mean velocity were higher in the a-tDCS condition when compared to the sham and control conditions (p<0.05). Meanwhile, the relative sEMG of the vastus lateralis, and RPE per set were lower in the a-tDCS condition when compared to sham and control conditions (p<0.05). This study suggest that a-tDCS-induced arousal over the left-M1 brain area thus improving the resistance exercise performances while reducing vastus lateralis sEMG, and RPE in mentally fatigued subjects.